An Assesment of the Policies Concerning the EU Sustainable Development Strategy - Arnold Weiszenbacher (CES Working Papers, 2014)
Sustainable development has been now for more than 15 years, at the center of the objectives of the EU, being already enshrined in the Amsterdam Treaty of 1997. The basic concern of this now ubiquitous term is to assure the current generation's demands will be fulfilled without endangering the needs of upcoming generations, sustainability being a key factor that affects both the financial market and the overall economy. The European Union has addressed this issue by developing a long term strategy, taking into account both economical, social, environmental and global governance factors and identifying seven key interrelated issues regarding climate change and clean energy, transport, consumption and production, the management and conservation of natural resources, public health, social inclusion and global poverty. This paper aims to present an overview of the current situation of the key challenges and their intersectoral measures and to determine the progress made in this area as well as to identify the key issues that offer the greatest amount of improvement and to recommend possible solutions to the aforementioned challenges. The methodology will benefit from data obtained and sampled from the Eurostat monitoring report, thus providing an accurate and transparent impartial analysis.
Keywords: A14; C40; E24; E31; E62; H31; H50; I12; I31; 330; sustainable development strategy; social inclusion; public health; climate change and energy Romania